2014
DOI: 10.1002/mds.26016
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical spectrum of impulse control disorders in Parkinson's disease

Abstract: Impulse control disorders (ICDs), including compulsive gambling, buying, sexual behavior, and eating, are a serious and increasingly recognized psychiatric complication in Parkinson's disease (PD). Other impulsive-compulsive behaviors (ICBs) have been described in PD, including punding (stereotyped, repetitive, purposeless behaviors) and dopamine dysregulation syndrome (DDS; compulsive PD medication overuse). ICDs have been most closely related to the use of dopamine agonists (DAs), perhaps more so at higher d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
233
0
18

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 279 publications
(261 citation statements)
references
References 75 publications
10
233
0
18
Order By: Relevance
“…Overall, patients in the ICB persister group were younger, pergolide use than ICB remitters. Younger age and pergolide use have been reported to be risk factors for the development of ICB (Antonini et al., 2017; Weintraub et al., 2006, 2015; Zurowski & O'Brien, 2015). Our findings suggest that these factors may also be related to the persistence of ICB.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Overall, patients in the ICB persister group were younger, pergolide use than ICB remitters. Younger age and pergolide use have been reported to be risk factors for the development of ICB (Antonini et al., 2017; Weintraub et al., 2006, 2015; Zurowski & O'Brien, 2015). Our findings suggest that these factors may also be related to the persistence of ICB.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of ICD or ICB has been reported to be 3.5%–58.3% in patients with Parkinson's disease (PD) (Antonini et al., 2017; Callesen, Weintraub, Damholdt, & Moller, 2014; Erga, Alves, Larsen, Tysnes, & Pedersen, 2017; Fan, Ding, Ma, & Chan, 2009; Rodriguez‐Violante, Gonzalez‐Latapi, Cervantes‐Arriaga, Camacho‐Ordonez, & Weintraub, 2014; Vela et al., 2016). ICB is an important nonmotor complication in patients with PD because it is associated with functional impairment, decreased quality of life and increased caregiver burden (Weintraub, David, Evans, Grant, & Stacy, 2015). Previous studies have shown that dopamine agonist (DA) use is the most consistent predictor of ICB (Weintraub, Koester, et al., 2010; Weintraub, et al., 2015; Zurowski & O'Brien, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations